(untitled) (New York, 1969)
Contents: Science: history of science, chemistry, earth science, life science, mathematics, physics, space sciences; Industry and technology: communications and transportation, energy and power sources, food and agriculture, machines and processes, materials and structures, weights and measures.
Keywords: Khoa học,Kỹ thuật,Science